2016
DOI: 10.1038/srep37103
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz molecular resonance of cancer DNA

Abstract: Carcinogenesis involves the chemical and structural alteration of biomolecules in cells. Aberrant methylation of DNA is a well-known carcinogenic mechanism and a common chemical modification of DNA. Terahertz waves can directly observe changes in DNA because the characteristic energies lie in the same frequency region. In addition, terahertz energy levels are not high enough to damage DNA by ionization. Here, we present terahertz molecular resonance fingerprints of DNA methylation in cancer DNA. Methylated cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(69 citation statements)
references
References 55 publications
(59 reference statements)
1
67
0
1
Order By: Relevance
“…A recent study involving methylated DNA, an aberrant DNA type found in early stage cancers, found it has a distinctive molecular resonance at 1.67 THz. By quantifying the THz spectral amplitudes at 1.67 THz, the degree of DNA methylation is ascertained and these results matched the gold-standard commercial enzyme-linked immunosorbent assay (ELISA) like reaction method well, and noting greater precision when using THz (11).…”
Section: Review Articlementioning
confidence: 99%
“…A recent study involving methylated DNA, an aberrant DNA type found in early stage cancers, found it has a distinctive molecular resonance at 1.67 THz. By quantifying the THz spectral amplitudes at 1.67 THz, the degree of DNA methylation is ascertained and these results matched the gold-standard commercial enzyme-linked immunosorbent assay (ELISA) like reaction method well, and noting greater precision when using THz (11).…”
Section: Review Articlementioning
confidence: 99%
“…Some of the features, such as non-ionizing, non-invasive, high penetration, high resolution and spectral fingerprinting [2,3], make THz wave a potential tool in biomedical field. Based on THz spectroscopy, many groups succeeded to obtain the fingerprint spectra of medicines [4][5][6][7][8], biomarkers [9][10][11][12][13], deoxyribonucleic acid (DNA) [14][15][16][17] and images of different cancers [18][19][20][21][22][23][24][25]. However, merely little work further studied the identification of biomarkers in actual biological samples, such as tissue, blood and urine.…”
Section: Introductionmentioning
confidence: 99%
“…[40] Although a substantial effort has been made to understand the toxic mechanism behind the interaction between membranes and Ab oligomers, it still remains elusive because Ab oligomer toxicity can be induced by size-dependent, composed residues, polymorphic structures, and diverse conformations of aggregates. [41][42][43][44] Therefore, characterizing the molecular architecture of Ab oligomers and formation pathways is critical to develop strategies for preventing, controlling, and regulating amyloid formation. In aqueous solutions or membranes, Ab oligomers possess polymorphic structural characteristics depending on various environmental conditions, such as ionic concentrations, pH, and thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%